Ветераны Удмуртии - Русских Петр Тимофеевич (60-летие Великой Победы, 2004)
Экземпляры: ф.1 (2005) / Инвентарный номер: zzzzzz14 / Цена: / Сис.шифр: 63.3 (2Рос=Удм) / Авт.знак: В 39 / ГРНТИ: 03.23.55 / ББК: 63.3 (2Рос=Удм)